Hydrolysis of vanadocene dichloride: A revisit - Honzíček, Jan; Růžičková, Zdeňka; Vinklárek, Jaromír (My University, 2016)
A key hydrolysis product of vanadocene dichloride was isolated and structurally characterized. The oligomeric character of the species precludes its detection by classical EPR spectroscopic tools. A detailed study of the with high purity reagents disproves appearance of Cp2V(OH)2, which was postulated previously based on mechanistic approach.
Hydrolýza vanadocen dichloridu
Keywords: vanadium; hydrolysis; vanad; hydrolýza